DIAGNOSTIC IMAGING MODALITIES FOR DETECTION OF LUNG METASTASES IN PATIENTS WITH DIFFRENTIATED THYROID CANCER - Т. М. Geliashvili; A. V. Vazhenin; Е. B. Vasilyeva; N. G. Afanasyeva (Сибирский онкологический журнал)
The aim of the study was to comparatively assess the efficacy of various diagnostic imaging modalities in detection of lung metastases of differentiated thyroid cancer. A retrospective analysis of the results of examination of 36 patients was carried out. Positron emission tomography/computed tomography (PET/ CT) with [F-18] fluorodeoxyglucose (FDG) was found to have the highest sensitivity for detection of lung metastases of differentiated thyroid cancer (100 %) followed by CT of the chest (95.5 %) and whole body scintigraphy (WBS) with 131I (66.7 %).